Adolescent Emotion Regulation Based on Emotional Intelligence and Self-Compassion - Bayu Dwisetyo; Faradilla Miftah Suranata; Cut Mutiya Bunsal (GLOBAL HEALTH SCIENCE GROUP, 2026)
Adolescence is a developmental stage characterized by social pressure, emotional turbulence, and identity exploration. Emotion regulation is a crucial skill that enables adolescents to adapt to social and academic demands. This study aimed to examine the role of emotional intelligence (EI) and self-compassion (SC) as predictors of emotion regulation among adolescents in Manado City. An explanatory quantitative design was employed, involving 300 high school students aged 15–19 years selected through stratified random sampling. Data were collected using the Schutte Emotional Intelligence Scale, the Self-Compassion Scale, and the Difficulties in Emotion Regulation Scale (DERS). Prior to the main study, all instruments were subjected to validity and reliability testing on a pilot sample of 30 adolescents with characteristics comparable to the study population. Item validity was assessed using item–total correlation, while reliability was evaluated using Cronbach’s alpha coefficient. Data were analyzed using descriptive statistics and multiple linear regression after meeting classical assumption tests. Indicated that the regression model was statistically significant (F = 412.245; p < 0.001), with a coefficient of determination (R²) of 0.727, indicating that EI and SC jointly explained 72.7% of the variance in emotion regulation. Partial analyses revealed that EI had a positive and significant effect on emotion regulation (B = 0.321; p < 0.001), whereas SC showed no significant effect (B = −0.009; p = 0.750). These findings indicate that emotional intelligence is the dominant factor in enhancing adolescents’ emotion regulation. Therefore, school-based mental health interventions should prioritize strengthening emotional intelligence, while fostering self-compassion may serve as a complementary long-term strategy.